Functionalization of Position 7 of Pyrazolo[1,5-a]pyrazines - Koidan, Georgyi; Tsyzoryk, Nazar; Rusanov, Eduard B.; Shishkina, Svitlana V.; Vovk, Mykhailo; Kostyuk, Aleksandr (SynOpen, 2024)
We report a straightforward formylation at position 7 of pyrazolo[1,5-a]pyrazine derivatives featuring substituents at the 2,3,4 positions. N,N,N′,1,1,1-Hexamethylsilanecarboximidamide exists in equilibrium with its carbene form due to 1,2-migration of the silyl group. The ensuing carbene can be inserted into the most acidic C–H group of the pyrazolo[1,5-a]pyrazines. The most acidic calculated pKa (DMSO) C–H group is at position 7 and does not depend significantly on the substituents. The reactions proceed in high yields affording aminals that can be hydrolyzed to the corresponding aldehydes. Methanolysis of the aminals affords the corresponding methylimines. The constitution of the aminals was unambiguously proved by X-ray crystal structure analysis of a set of derivatives. The method is simple, often does not require even solvents, and can be extended to other heterocyclic compounds.
Keywords: pyrazolo[1,5-a]pyrazine; diaminomethylation; aldehyde; carbene; C–H insertion